Flavor of the month : why smart people fall for fads - Best, Joel (University of California Press, 2006)
Joel Best explores the range of institutional fads, analyses the features of our culture that foster them, and identifies the major stages of the fad cycle: emerging, surging, and purging. He examines the causes and consequences of fads and suggests ways of fad-proofing our institutions.